Human tolerogenic dendritic cell subtypes exert divergent effects on induction of cytotoxic CD4+ T cells - Barran, Gabrielle; Naamane, Najib; Baru, Abdul Mannan; Anderson, Amy E.; Falconer, Jane; Hilkens, Catharien M. U. (Frontiers in Immunology, 2025)
Tolerogenic dendritic cells (tolDC) are currently in clinical trials for the treatment of autoimmune diseases such as rheumatoid arthritis and multiple sclerosis. The methods for producing therapeutic tolDC vary widely, with little being known about the commonalities and differences of distinct cell products in terms of their regulatory actions on CD4+ T cells. We compared human monocyte-derived tolDC generated with vitamin D3 alone or in combination with dexamethasone. We found marked differences in the surface expression of HLA-DR and immune regulatory molecules, but also found commonalities, e.g. a strongly reduced capacity to produce interleukin-12 and a concomitant decreased ability to induce interferon-γ secretion by allogeneic CD4+ T cells. To gain a deeper understanding of how these tolDC types exert their regulatory effects, we co-cultured them with CD4+ T cells from rheumatoid arthritis patients or healthy controls and analysed the gene expression profile and function of the responding T cells. We found that tolDC generated with vitamin D3 alone, but not in combination with dexamethasone, induced potent cytotoxic activity in the responding CD4+ T cells as demonstrated by an enhanced cytotoxic gene signature, increased levels of intracellular granzyme B, and superior cytotoxic activity towards myeloid and B cells. These data identify cytotoxicity as an atypical CD4+ T helper cell effector function induced by some but not all tolDC types, with implications for their individual clinical applications.